Case Report: Surgery for proximal gastric cancer with splenic artery aneurysm: approach and complication mangement - Shu, Xuerui; Xiang, Fu; Xu, Xuedong; Jing, Lin; Tian, Riyu; Xia, Yiao (Frontiers in Oncology, 2025)
IntroductionGastric cancer surgery is gradually shifting from extensive, standardized operations to individual, precise procedures. The two surgical options for proximal gastric cancer are total gastrectomy and proximal gastrectomy. In recent years, proximal gastrectomy has gained wider acceptance in clinical practice, with increasingly relaxed indications. The present report describes an extremely rare clinical case of proximal gastric cancer.Case presentationA 64-year-old man with proximal gastric cancer after splenic artery aneurysm embolization underwent proximal gastrectomy with preservation of the short gastric vessels to retain the spleen. Despite the difficult treatment process, the patient achieved a favorable outcome at the 10-month follow-up.ConclusionThis report provides a valuable reference for the individualized treatment of proximal gastric cancer, highlighting the importance of considering potential complications such as external pressure from anatomical anomalies in the postoperative management of gastric cancer.